Gold nanoparticles–conjugated quercetin induces apoptosis via inhibition of EGFR/PI3K/Akt–mediated pathway in breast cancer cell lines (MCF‐7 and MDA‐MB‐231) - Balakrishnan, Solaimuthu; Mukherjee, Sudip; Das, Sourav; Bhat, Firdous Ahmad; Raja Singh, Paulraj; Patra, Chitta Ranjan; Arunakaran, Jagadeesan (Cell biochemistry and function, 2017)
Epidermal growth factor plays a major role in breast cancer cell proliferation, survival, and metastasis. Quercetin, a bioactive flavonoid, is shown to exhibit anticarcinogenic effects against various cancers including breast cancer. Hence, the present study was designed to evaluate the effects of gold nanoparticles–conjugated quercetin (AuNPs‐Qu‐5) in MCF‐7 and MDA‐MB‐231 breast cancer cell lines. Borohydride reduced AuNPs were synthesized and conjugated with quercetin to yield AuNPs‐Qu‐5. Both were thoroughly characterized by several physicochemical techniques, and their cytotoxic effects were assessed by MTT assay. Apoptotic studies such as DAPI, AO/EtBr dual staining, and annexin V‐FITC staining were performed. AuNPs and AuNPs‐Qu‐5 were spherical with crystalline nature, and the size of particles range from 3.0 to 4.5 nm. AuNPs‐Qu‐5 exhibited lower IC50 value compared to free Qu. There was a considerable increase in apoptotic population with increased nuclear condensation seen upon treatment with AuNPs‐Qu‐5. To delineate the molecular mechanism behind its apoptotic role, we analysed the proteins involved in apoptosis and epidermal growth factor receptor (EGFR)–mediated PI3K/Akt/GSK‐3β signalling by immunoblotting and immunocytochemistry. The pro‐apoptotic proteins (Bax, Caspase‐3) were found to be up regulated and anti‐apoptotic protein (Bcl‐2) was down regulated on treatment with AuNPs‐Qu‐5. Additionally, AuNPs‐Qu‐5 treatment inhibited the EGFR and its downstream signalling molecules PI3K/Akt/mTOR/GSK‐3β. In conclusion, administration of AuNPs‐Qu‐5 in breast cancer cell lines curtails cell proliferation through induction of apoptosis and also suppresses EGFR signalling. AuNPs‐Qu‐5 is more potent than free quercetin in causing cancer cell death, and hence, this could be a potential drug delivery system in breast cancer therapy.